Development of IL-5 Receptor Antagonists - Uings, I.; McKinnon, M. (Current Pharmaceutical Design, 2002)
A wealth of both clinical and pre-clinical data has strongly implicated the eosinophil in the pathogenesis of asthma, highlighting this cell type as a potential target for novel anti-inflammatory approaches to asthma therapy. The Th2 lymphocyte derived cytokine Interleukin-5 (IL-5) has emerged as the key regulator of eosinophil production, thus identifying IL-5 as the principal molecular target for therapeutic intervention. This review highlights both the pharmaceutical approaches, and the major challenges, to the identification of small molecule and protein antagonists of the IL-5 receptor. Using examples of known inhibitors we discuss their current status and highlight the major development hurdles in progressing these molecules into the market place.
Keywords: constrained peptides